Технологические комплекты малогабаритного оборудования с использованием бетоносмесителей, работающих в каскадном режиме - Емельянова, И. А.; Задорожный, А. А.; Блажко, В. В.; Анищенко, А. И. (НТУ "ХПИ", 2010)
Представлены технологические комплекты малогабаритного оборудования для выполнения торкрет-работ, транспортирования бетонных смесей и приготовления сталефибробетонных смесей. Комплекты предназначены для работы в условиях строительных площадок различного назначения, а также в условиях производства. Приведены их технические характеристики. Обращено внимание на конструктивные особенности машин и оборудования входящих в состав комплектов.

The technological packages small equipment to carry out spray operations, transportation of concrete mixtures and cooking concrete with steel fiber mixtures. Kits are designed to work in construction sites for various purposes, as well as in industry. Given their technical characteristics. The attention to design features of machinery and equipment belonging to the sets. Attention is paid to the new mixer is used in technological units operating in cascade mode and allow the preparation of the mixture of different mobility, including slow-moving. Emphasis is placed on some of the results of research equipment and machinery technology sets
Technological complete sets of small equipment with the use of concrete mixers, workings in cascade mode
Keywords: малогабаритное оборудование; бетонные смеси; сталефибробетонные смеси; комплекты